Coupling sensitivity in concentric metal–insulator–semiconductor tunnel diodes by controlling the lateral injection electrons - Kung-Chu Chen; Jenn-Gwo Hwu (AIP Advances, 2020)
Coupling sensitivity between two Al–SiO2–pSi metal–insulator–semiconductor tunnel diodes (MISTDs) was examined by sweeping bias voltage on one MISTD and detecting ground current or floating voltage at another nearby MISTD with the substrate being grounded when performing the measurement. A strong coupling phenomenon between two concentric MISTDs was observed in this work. The experiment shows that the coupling sensitivities have a maximum value at a range of about −0.4 V to −0.7 V and turn to minimum at about the flat band voltage (∼−0.9 V) when bias was swept from 0 to −1 V. The simulation result also shows a maximum lateral diffuse current when the MISTD was biased at about −0.7 V and turns to a small value near the flat band voltage. It was speculated that the lateral electron flow due to piled-up injection electrons is the origin of the observed highly sensitive coupling phenomenon. A possible mechanism was proposed to explain the turnaround phenomenon.